Rapid screening methods for yeast sub‐metabolome analysis with a high‐resolution ion mobility quadrupole time‐of‐flight mass spectrometer. (2nd May 2019) - Mairinger, Teresa; Kurulugama, Ruwan; Causon, Tim J.; Stafford, George; Fjeldsted, John; Hann, Stephan
Abstract : Rationale: The wide chemical diversity and complex matrices inherent to metabolomics still pose a challenge to current analytical approaches for metabolite screening. Although dedicated front‐end separation techniques combined with high‐resolution mass spectrometry set the benchmark from an analytical point of view, the increasing number of samples and sample complexity demand for a compromise in terms of selectivity, sensitivity and high‐throughput analyses. Methods: Prior to low‐field drift tube ion mobility (IM) separation and quadrupole time‐of‐flight mass spectrometry (QTOFMS) detection, rapid ultrahigh‐performance liquid chromatography separation was used for analysis of different concentration levels of dansylated metabolites present in a yeast cell extract. For identity confirmation of metabolites at the MS2 level, an alternating frame approach was chosen and two different strategies were tested: a data‐independent all‐ions acquisition and a quadrupole broad band isolation (Q‐BBI) directed by IM drift separation. Results: For Q‐BBI analysis, the broad mass range isolation was successfully optimized in accordance with the distinctive drift time to m / z correlation of the dansyl derivatives. To guarantee comprehensive sampling, a broad mass isolation window of 70 Da was employed. Fragmentation was performed via collision‐induced dissociation, applying a collision energy ramp optimized for the dansyl derivatives. Both approaches were studied in terms of linear dynamic range and repeatability employing ethanolic extracts of Pichia pastoris spiked with 1 μM metabolite mixture. Example data obtained for histidine and glycine showed that drift time precision (<0.01 to 0.3% RSD, n = 5) compared very well with the data reported in an earlier IM‐TOFMS‐based study. Conclusions: Chimeric mass spectra, inherent to data‐independent analysis approaches, are reduced when using a drift time directed Q‐BBI approach. Additionally, an improved linear dynamic working range was observed, representing, together with a rapid front‐end separation, a powerful approach for metabolite screening.